Prevalence of overweight and obesity in preschool children (2–5 year-olds) in Birjand, Iran - Fatemeh Taheri (BMC Research Notes, 2012)
Abstract Background Childhood overweight and obesity have increased progressively in developing countries and nowadays they are considered as a global epidemic. The aim of the present study was to determine prevalence of overweight and obesity in 2–5 year-old children in kindergartens of Birjand in 2008. Findings This cross- sectional and descriptive- analytical study was conducted on 500 children, who were 2–5 years-old, in kindergartens of Birjand selected through census. It was found that prevalence of overweight was 10.6% (11.7% in females and 9.6% in males) and obesity 7.6% (6.3% in females and 9.6% in males). Prevalence of overweight and obesity were statistically significant regarding birth weight, mother's occupation and father's level of education. Conclusion Prevalence of overweight and obesity in pre-schoolchildren is more than that of 7–18 year-old group in Birjand, but it is less than the result of similar studies in Tehran and most studies in other countries. Further studies are recommended to identify risk factors in obese children. Periodic studies are necessary to compare the changes in prevalence of obesity in children in future.